The Impact of Digital Marketing Strategies on Sustainable Tourism Development - Arjuna Ranatunga; Kumar Sangakkara; Mahela Jayawardene (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This paper examines the influence of digital marketing strategies on sustainable tourism. By analyzing case studies from leading tourism organizations, the research identifies effective practices, such as content marketing, social media engagement, and influencer collaborations. The findings reveal that digital marketing not only boosts visibility but also promotes responsible tourism behaviors among travelers.